Variação linguística na língua portuguesa: uma proposta de ensino dos modos verbais com uso de banco de dados linguísticos - Silva, Raimundo Gouveia da (2018)
This paper aims to present a teaching proposal for the study of verbal paradigms, indicative and subjunctive from the Portuguese Language, with emphasis on work with linguistic variation. To achieve this goal, we created a Language Database, composed of samples from the center area of the Cazumbá-Iracema Extractive Reserve, located in Acre, which served as supporting material. For collection and organization of the Banco Reci, we considered as variables the age range, sex and education level, based on sociolinguistic standards; empirical foundations for a theory of linguistic change; variationist sociolinguistics. For the collection of the linguistic data, 36 informants were interviewed, divided into three social cells, forming the criteria for obtaining the data: sex (male and female); age (from the age of 15); education level (Basic Education and non-literate). With emphasis on the Data Driven Learning and Constructive Alignment approach, discovery learning activities were developed through direct consultation of the compiled corpus. The proposal was developed with a group of high school students, from the center area of the Reserve. The results evidenced contributions in the learning by discovery, through the valorization of the contact with data of the language in its authentic use and with activities that potentiate the construction of the knowledge and are able to develop the collaborative work, to help the understanding and reflection on uses of the mother tongue , according to the normative grammar and the functional use of the mother language, to promote the interaction between the students and the understanding about the social factors that corroborate in the linguistic variation of the reserve. This work has as educational products a tutorial and the Linguistic Database Reci.